The professional ScrumMaster's handbook : a collection of tips, tricks, and war stories to help the professional ScrumMaster break the chains of traditional organization and management - Viscardi, Stacia (Professional expertise distilled., 2013)
Focusing on the ScrumMaster role and responsibilities, this book presents solutions and ideas for common problems, improving the overall methodology of a ScrumMaster's approach. The Professional ScrumMaster's Handbook is for anybody who wishes to be a true ScrumMaster as the role was originally intended - a fearless, professional, change facilitator. This book extends your working knowledge of Scrum to explore other avenues and ways of thinking to help teams and organizations reach their full potential.